Extracellular Alterations in pH and K+ Modify the Murine Brain Endothelial Cell Total and Phospho-Proteome - Jared R. Wahl; Anjali Vivek; Seph M. Palomino; Moyad Almuslim; Karissa E. Cottier; Paul R. Langlais; John M. Streicher; Todd W. Vanderah; Erika Liktor-Busa; Tally M. Largent-Milnes (MDPI AG, 2022)
Pathologies of the blood-brain barrier (BBB) have been linked to a multitude of central nervous system (CNS) disorders whose pathology is poorly understood. Cortical spreading depression (CSD) has long been postulated to be involved in the underlying mechanisms of these disease states, yet a complete understanding remains elusive. This study seeks to utilize an in vitro model of the blood-brain barrier (BBB) with brain endothelial cell (b.End3) murine endothelioma cells to investigate the role of CSD in BBB pathology by characterizing effects of the release of major pronociceptive substances into the extracellular space of the CNS. The application of trans-endothelial electrical resistance (TEER) screening, transcellular uptake, and immunoreactive methods were used in concert with global proteome and phospho-proteomic approaches to assess the effect of modeled CSD events on the modeled BBB in vitro. The findings demonstrate relocalization and functional alteration to proteins associated with the actin cytoskeleton and endothelial tight junctions. Additionally, unique pathologic mechanisms induced by individual substances released during CSD were found to have unique phosphorylation signatures in phospho-proteome analysis, identifying Zona Occludins 1 (ZO-1) as a possible pathologic "checkpoint" of the BBB. By utilizing these phosphorylation signatures, possible novel diagnostic methods may be developed for CSD and warrants further investigation.